(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Episiotomy is a commonly performed surgical procedure, particularly in nulliparous women during 2nd stage of labour. Some complications, such as infection, perineal pain, trauma, etc., led to some limitations against routine episiotomy. Considering the adverse effects of routine episiotomy, restrictive episiotomy is under trial for better outcomes. This study aimed to compare the fetometarnal outcomes in routine versus restrictive episiotomy in primigravid women at Chittagong Medical College Hospital. Materials and methods: One hundred primigravid women with term pregnancy were included in this quasi- experimental study. They were randomly allocated into two equal groups, A and B. In Group A, delivery was conducted with routine episiotomy. In Group B, delivery was performed with restrictive episiotomy. Maternal and fetal outcomes were observed and compared between the two groups. Results: In Group A, 24% had experienced extension of episiotomy wound; in Group B, 42% had 1st-degree perineal tear, and 08% had 2nd-degree perineal tear. A total of 07 (14%) patients needed episiotomy, 4 women for imminent perineal tear and 3 for maternal exhaustion. Wound infection was 2%, only in the routine episiotomy group. NICU admission was required for 18% and 12% of the neonates in Groups A and B, respectively. Conclusion: As immediate outcomes following routine use of episiotomy are the same as those of restrictive use, a policy of routine episiotomy should be abandoned in primigravidae; instead, a restricted episiotomy approach should be followed. JCMCTA 2023 ; 34 (2) : 85-88